The feeling of fear of families with stroke survivors to the threat of COVID-19 - Sari, Lusia Lero Maya; Ratrikaningtyas, Prima Dhewi; Supriyati (BKM Public Health and Community Medicine, 2022)
Purpose: The purpose of this study was to explore the fear feeling of family and the threat of COVID-19 in stroke survivors. Methods: This study uses a qualitative method with a phenomenological research design. This study is a nested research in the population of HDSS Sleman, so it uses secondary data from stroke survivors' information. The research informants amounted to 8 people. Data collection was carried out in July-August 2021 in Kecamatan Depok Kabupaten Sleman. In-depth interviews and photo documentation were carried out in data collection. Data were analyzed using OpenCode version 4.2. Results: The health status of the stroke survivors at the time of the interview had recovered before the pandemic, died during the pandemic but was not caused by COVID-19, and were still in a state of stroke. All informants or families of stroke survivors showed the same fear response to the threat of COVID-19. Families who care for stroke survivors think that those who are at risk and vulnerable to being exposed to COVID-19 are older people and those who have comorbidities. Fear arises because it is influenced by the perception of oneself and the surrounding environment. There are fears in the form of the assumption that they might be exposed when carrying out examinations and treatment at health facilities, fear of doing swabs, and the financing of COVID-19 testing and the number of positive cases. Conclusion: The fear of the vulnerability of stroke survivors when exposed to the COVID-19 virus is shown by families of stroke survivors by avoiding visits to health facilities, be it puskesmas or hospitals, and choosing to anticipate themselves at home. The fear of the families of stroke survivors must be a concern for the healthcare institutions that protect them so that treatment and health services for stroke survivors with comorbidities during the pandemic can still be achieved.